NITROIMIDAZOLES XI [I]. SYNTHESES OF DISUBSTITUTED NITROIMIDAZOLYLQUINOLINES (Journal of Sciences, Islamic Republic of Iran)
Reaction of substituted-aniline (8) with ethyl (l-methyl-5-nitroimidazole-2- carbonyl) acetate (9) gave 4-hydroxy-2-(l-methyl-5-nitro-2-imidazolyl)- substituted-quinolines (lo), which were converted to compound 11 with phosphorus oxychloride. Substituted-2-(l-methyl-5-nitro-2-imidazo1yl)-4.- methyl-(or phenyl-) quinolines (14) were prepared through the reaction of 2- acetyl-5-nitro-1-methyl-imidazole (13) with 0-aminoacetophenones (or Oaminobenzophenones) in acid medium